Analysis of Potential Mechanism of Herbal Formula Taohong Siwu Decoction against Vascular Dementia Based on Network Pharmacology and Molecular Docking. (23rd January 2023) - He, Ruixin; He, Fengjiao; Hu, Zhenliang; He, Yifang; Zeng, Xinting; Liu, Yao; Tang, Liang; Xiang, Ju; Li, Jianming; He, Binsheng; Xiang, Qin
Abstract : Vascular dementia (VaD) is the second most prevalent dementia, which is attributable to neurovascular dysfunction. Currently, no approved pharmaceuticals are available. Taohong Siwu decoction (TSD) is a traditional Chinese medicine prescription with powerful antiapoptosis and anti-inflammatory properties. In this study, a network pharmacology approach together with molecular docking validation was used to explore the probable mechanism of action of TSD against VaD. A total of 44 active components, 202 potential targets of components, and 3, 613 VaD-related targets including 161 intersecting were obtained. The potential chemical components including kaempferol, baicalein, beta-carotene, luteolin, quercetin, and beta-sitosterol involved in the inflammatory response, oxidative stress, and apoptosis might have potential therapeutic effects on the treatment of VaD. The potential core targets including AKT1, CASP3, IL1 β, JUN, and TP53 associated with cell apoptosis and inflammatory might account for the essential therapeutic effects of TSD in VaD. The results indicated that TSD protected against VaD through multicomponent and multitarget modes. Though the detailed mechanism of action of various active ingredients needs to be further illustrated, TSD still showed a promising therapeutic agent for VaD due to its biological activity.